SIRT3 consolidates heterochromatin and counteracts senescence. Issue 8 (12th March 2021) - Diao, Zhiqing; Ji, Qianzhao; Wu, Zeming; Zhang, Weiqi; Cai, Yusheng; Wang, Zehua; Hu, Jianli; Liu, Zunpeng; Wang, Qiaoran; Bi, Shijia; Huang, Daoyuan; Ji, Zhejun; et al.
Abstract: Sirtuin 3 (SIRT3) is an NAD + -dependent deacetylase linked to a broad range of physiological and pathological processes, including aging and aging-related diseases. However, the role of SIRT3 in regulating human stem cell homeostasis remains unclear. Here we found that SIRT3 expression was downregulated in senescent human mesenchymal stem cells (hMSCs). CRISPR/Cas9-mediated depletion of SIRT3 led to compromised nuclear integrity, loss of heterochromatin and accelerated senescence in hMSCs. Further analysis indicated that SIRT3 interacted with nuclear envelope proteins and heterochromatin-associated proteins. SIRT3 deficiency resulted in the detachment of genomic lamina-associated domains (LADs) from the nuclear lamina, increased chromatin accessibility and aberrant repetitive sequence transcription. The re-introduction of SIRT3 rescued the disorganized heterochromatin and the senescence phenotypes. Taken together, our study reveals a novel role for SIRT3 in stabilizing heterochromatin and counteracting hMSC senescence, providing new potential therapeutic targets to ameliorate aging-related diseases.